Introduction to No. 1, Part two: Developing Moral Competence, Perfecting Selfhood, Practicing Forgiveness - Bardziński, Filip; Dutka, Joanna (ETHICS IN PROGRESS, 2016)
The introductioń to Ethics in Progress Special Issue, Vol. 7(1), No. 2 is given, with brief exposes on the articles present in the section.